Warehouse management : b the definitive guide to improving efficiency and minimizing costs in the modern warehouse - Richards, Gwynne (Kogan Page, 2022)
"Modern warehouses are capitalizing on cutting-edge technologies, new operating models and innovative practices to maximize their role in the wider supply chain. Understand how to successfully manage these warehouses with this bestselling guide.Warehouse Management guides the reader through all aspects of successful managing a warehouse, its operations and distribution. This bestselling book covers an extensive range of key topics from defining the modern warehouse, detailing management processes, strategies and practices to outlining how to tackle environmental challenges to ensure a sustainable supply chain. With practical insights into how to improve operating costs, increase efficiency and reduce costs, this is a must read for optimizing warehouse performance. The fourth edition of Warehouse Management is fully updated to include up to date information across the board. The latest technologies in warehousing, such as robotics, cobots and AI, are explained and their impact is situated alongside discussions on the future of warehousing. Gwynne Richards provides expert advice with clear and easy to grasp solutions. New and updated online resources provide support to readers"-- c Provided by publisher